Limit Solutions for Finite Horizon Bargaining Problems - Haruo Imai; Hannu Salonen (Aboa Centre for Economics (ACE), 2009)
We investigate a random proposer bargaining game with a dead line. A bounded time interval is divided into bargaining periods of equal length and we study the limit of the subgame perfect equilibrium outcome as the number of bargaining periods goes to infinity while the dead line is kept fixed. This limit is close to the Raiffa solution when the time horizon is very short. If the dead line goes to infinity the limit outcome converges to the time preference Nash solution. The limit outcome is given an axiomatic characterization as well.
Keywords: C71; C72; C78; 330; Nash solution; Raiffa solution; bargaining